The Influence of the Green Product Milo UHT Drink on Consumer Purchase Interest Using the Simple Regression Analysis Method - Nugraha, Isna; Ramadhan , Gilang (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2024)
This research aims to evaluate the influence of Green Product Milo packaging on consumer buying interest. A quantitative descriptive research method was used by applying path analysis through a questionnaire distributed to 120 Milo consumer respondents. The research results show that Green Product adoption has a positive effect on repurchase intention. The implication is that companies need to maintain Green Products by continuing to innovate quality and environmentally friendly products and increasing promotions through potential media such as Instagram. Statistical analysis shows that there is a significant relationship between the level of product completeness and consumer attractiveness (p < 0.05). Although the correlation between the level of environmentally friendly products and purchase intention is relatively weak (correlation 0.411), the regression model shows a positive influence. From the results of ANOVA calculations, this regression can be used to predict purchasing interest in environmentally friendly products. It can be concluded that Green Products have a significant influence on consumer buying interest by contributing 16.9% to the variability in buying interest. This research provides an important contribution to companies in making strategic decisions related to product development and marketing.